ISOLASI, IDENTIFIKASI, DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA GOLONGAN TRITERPENOID PADA RIMPANG TEMU PUTIH (Curcuma zedoaria (Berg.) Roscoe) - Wiwik Susanah Rita (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Isolation, identification, and antibacterial activity examination of triterpenoid compounds from rhizome ofCurcuma zedoaria (Berg.) Roscoe have been conducted. Maseration of 600 g dry powder of those rhizome using nhexaneand ethanol respectively yielded 9,79 g of n-hexane extract and 23,45 g of ethanol extract. The ethanolextract containing triterpenoids was dissolved into ethanol-water (7:3) mixture. The mixture was evaporated toremove the ethanol and then partitioned by chloroform. Hence, two extract were produced i.e., chloroform and waterextract. The n-hexane and chloroform extracts obtained contained triterpenoids based on fitochemical test ofLieberman-Burchard. Antibacterial test showed that only chloroform extract was active with inhibition zone of 2 mmfor Staphylococcus aureus.Compound separation of the chloroform extract using column chromatography produced 0,44 g brownisolate which contained triterpenoids (fraction F1). The isolate inhibited the growth of Staphylococcus aureus andEscherichia coli with weak inhibition zone at 500 ppm and 1000 ppm. Infrared spectra indicated that the isolate wasa carboxylic acids triterpenoids, with characteristic functional groups of –OH bonded, –CH, C=O of carboxylic acids,–C=C, –CH2, –CH3, and C–O alcohol. The ultraviolet-visible spectra showed maximum absorption at 242 nm and280 nm.